Preparation and characterization of grease using used cooking oil and used engine oil - Ong, Huei Ruey; Wan Mohd Eqhwan, Iskandar; Goh, Choon Phang; Hong, Chi Shein; Khan, Md. Maksudur Rahman; Mohammad Khairul Anuar, Mohamed (IOP Publishing, 2020)
Used engine oil (UEO) and used cooking oil (UCO) are treated as hazard to human health and the environment. A proper management of them are necessary to prevent its adverse impacts. This study is to examine the potential of UEO and UCO used as raw material in preparing grease. UEO and UCO has the potential in replacing the base fluid (mineral oil) and thickener precursor, respectively in conventional grease making. The thickener has been prepared by using calcium hydroxide and sodium hydroxide to react with UCO with the ratio of 1:2 (hydroxide: UCO) and denoted as calcium and sodium thickener, respectively. In grease making, different concentration of thickener (20, 30 and 40%) was used to react with UEO for 180 min at 160 – 180 °C. The formation of grease is confirmed by FTIR analysis, where a new peak was form in 1377 cm−1 – 1423 cm−1. Apart from that it was found that, 20% calcium thickener with 80% UEO grease and 40% sodium thickener with 60% UEO grease were comparable with commercial grease in term of dropping point and water resistance properties.